Rorschach Evaluation of Personality and Emotional Characteristics in Adolescents With Migraine Versus Epilepsy and Controls - Balottin, Laura; Mannarini, Stefania; Candeloro, Daniela; Mita, Alda; Chiappedi, Matteo; Balottin, Umberto (Frontiers in Neurology, 2018)
The literature examining primary headache, including migraine, in adolescents, has pointed out the key role played by a wide range of psychiatric disorders in reducing the patients’ quality of life. Moreover, pioneering studies showed that preexisting personality characteristics, specific emotion regulation styles and psychological-psychiatric difficulties are likely to increase the risk of the onset, maintenance and outcome of headache. Still personality issues in migraine have been poorly studied, in particular in children and adolescents. This study aims therefore to investigate the specific characteristics of personality, and in particular emotion regulation and coping strategies, in adolescent with migraine, comparing them with age-matched patients with idiopathic epilepsy and healthy adolescents. 52 adolescents (age: 11-17) were assessed using a multi-method test battery, which included a self-report questionnaire (the Youth Self-report), a proxy-report (Child Behavior Checklist) along with a projective personality test, the Rorschach Test, administered and scored according to the Exner Comprehensive System. The results showed specific personality characteristics in adolescents with migraine, revealing a marked difficulty in modulating and regulating affections through thoughts and reflections, resorting instead to impulsive acts and maladaptive coping strategies, thus revealing a vague and immature perception of reality. Differently from adolescents belonging to the general population but similarly to patients with epilepsy, adolescents with migraine perceive a high situational stress, probably related to the condition of suffering from chronic disease. They have therefore a lower self-consideration and self-esteem along with a poorer insight regarding themselves as well as the relations with others. In line with previous findings, these preliminary results suggest the need for further research on ample samples, using also standardized projective test in order to better understand the pathogenesis of psychological difficulties in patients with migraine. As a clinical implication, the results seem to indicate that providing a psychological integrated approach can play a pivotal role in the assessment and treatment of adolescent with migraine, in order to improve the outcome and the quality of life of the young patients.